Integration of digital learning in islamic religious education curriculum: challenges and opportunities - Moh. Yahya Obaid; Achmad Ruslan Afendi; Mulahizhun Amien; Badrudin Badrudin; Aliah Bagus Purwakania Hasan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study explores the integration of digital learning into the Islamic Religious Education (IRE) curriculum, focusing on the challenges and opportunities presented by this process. The main issue addressed is the slow adoption of digital tools in Islamic education, despite the growing reliance on technology in other educational sectors. The objective of this research is to examine how digital learning can enhance student engagement, accessibility, and interactivity in IRE, while maintaining the integrity of Islamic teachings. The study uses a library research method, collecting data from relevant books, journal articles, and previous studies related to digital learning and Islamic education. The findings reveal that digital tools can significantly improve the learning experience by offering interactive content, personalized learning paths, and access to educational resources beyond traditional classrooms. However, challenges such as inadequate infrastructure, resistance to change from educators, and concerns over preserving the spiritual aspects of Islamic education are identified. The research concludes that, while the integration of digital learning into IRE offers considerable benefits, overcoming these challenges is essential for its successful implementation. Recommendations include investing in infrastructure, providing teacher training, and ensuring the alignment of digital tools with Islamic educational values